THE ROLE OF COMMERCIAL BANKS IN FINANCIAL SUPPORT OF BUSINESS ACTIVITY (Conferencea, 2024)
Today, the effectiveness of foreign economic activity of business entities depends not only on their internal financial capabilities and efficiency, but also on the level of development of financial and credit institutions involved in financing their activities.